TWO PHASE FLOW IN CO2/BRINE SYSTEM WITH SALT PRECIPITATION - PAU , JION SEAN (2014)
As a developing industrialized nation, Malaysia pledged a 40% reduction in carbon by 2020. Carbon capture and storage in geological sites (CCGS) is a promising technology to reduce CO2 release into the atmosphere by storing CO2 in the underground geological formation. As supercritical CO2 and brine has distinctive density, buoyant force is produced and CO2, being the less dense phase will flow upward when replacing brine. The formation's properties will also affect the flow of CO2. Dry C02 will evaporate the brine water and cause formation of salt which will affect the permeability of saline aquifer. The aim of the research work is io model and evaluate the migration of CO2 when displacing brine water and also to evaluate the effects of salt precipitation on CO2 injection and injectivity impairment of saline aquifer. The pressure and saturation equation for two phase flow is discretized using implicit pressure and explicit saturation (IMPES), fully-implicit (FI) and mixed and hybrid finite element method (MHFEM). MHFEM has the advantage of ensuring the continuity in between the elements. The discretized equation is implemented in Matlab 2012b software.